Clinical and endocrine features of orthostatic intolerance detected in patients with long COVID - Kato, Atsushi; Tokumasu, Kazuki; Yamamoto, Koichiro; Otsuka, Yuki; Nakano, Yasuhiro; Honda, Hiroyuki; Sunada, Naruhiko; Sakurada, Yasue; Matsuda, Yui; Hasegawa, Toru; Takase, Ryosuke; Ueda, Keigo; et al. (Scientific reports, 2024)
Orthostatic intolerance (OI) is a key symptom of long COVID; however, the pathophysiology remains unknown. Among 688 long COVID patients who visited our clinic during the period from February 2021 to April 2023, 86 patients who were suspected of having OI and who underwent an active standing test (ST) were investigated to elucidate the clinical characteristics of OI in patients with long COVID. Of the 86 patients, 33 patients (38%) were ST-positive. Nausea and tachycardia in daily life were frequent complaints in the ST-positive group. The increase in heart rate (HR) during the ST was significantly greater during a 10-min period after standing in the ST-positive group (+ 30 bpm) than in the ST-negative group (+ 16 bpm). The initial increase in diastolic blood pressure (DBP) just after standing was significantly greater in the ST-positive group (+ 14 mmHg) than in the ST-negative group (+ 9 mmHg). Serum cortisol levels in the ST-positive patients aged over 20 years were higher and growth hormone levels in the patients under 20 years of age were lower than those in the ST-negative group. Autonomous nervous symptoms, transient DBP rise with increasing HR after standing, and endocrine dysfunctions are helpful for detecting OI related to long COVID.